Identifikasi Drug-Related Problems (DRPs) pada Pasien Rawat Inap Stroke Iskemik dan Hemoragik: Studi Observasional Retrospektif di Rumah Sakit Rujukan - Marizah Riska Putri; Erika Lutfia Tunnisaq (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Stroke remains a leading cause of mortality and long-term disability worldwide, requiring complex pharmacotherapy regimens that significantly increase the risk of Drug-Related Problems (DRPs). This study aimed to identify, categorize, and analyze the prevalence and patterns of DRPs among stroke inpatients using a retrospective observational approach. Data were collected from medical records of 98 hospitalized stroke patients treated between January and December 2025 at a referral hospital. DRPs were classified based on the Pharmaceutical Care Network Europe (PCNE) V9.1 system. The patient cohort comprised 55.1% males and 44.9% females, with 57.1% aged ≥ 60 years. Ischemic stroke accounted for 91.8% of cases, while hemorrhagic stroke constituted 5.1%. Hypertension (69.4%) and Type 2 Diabetes Mellitus (28.6%) were the predominant comorbidities. A total of 135 DRP events were identified in 82 patients (83.7%). The most frequent categories were potential drug–drug interactions (36.3%), untreated indications or need for additional therapy (29.6%), inappropriate drug selection (19.3%), and inappropriate dosing, including absent renal-dose adjustment (14.8%). Critical potential interactions included co-administration of clopidogrel with omeprazole and NSAIDs with antihypertensives. Untreated indications mainly involved the absence of high-intensity statin therapy in ischemic stroke patients. In conclusion, DRPs are highly prevalent among stroke inpatients, particularly driven by polypharmacy and complex comorbidities. Clinical pharmacist interventions are crucial to optimize therapeutic outcomes and minimize adverse drug events